The Private Security and the Uniform System of Cross-Border (Security) of Transport of Cash between euro-area Member States - Stajić, Ljubomir; Mandić, Goran; Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
With the creation of the European Union (EU), the signing of the Maastricht Agreement, the introduction of the single market and freedom of movement of labor and the introduction of the euro as a common currency, the problem of cross-border road transport of cash and valuables between eurozone members arose. This is because almost all EU member states had more or less different solutions and practices for this type of transport. The EU tried to solve the problem by adopting Regulation No. 1214/2011 on professional cross-border road transport of cash between euro-area Member States. The mentioned Regulation successfully solved many problems related to this issue, such as: issuance of appropriate permits (licences), maximum duration of delivery, rights and obligations of teams, necessary knowledge and skills of security staff, carrying weapons in the host country, type and equipment of vehicles, mutual information, etc. Although the intention was to establish a unified system of cross-border money transport, in addition to significant progress in the functioning of private security, it can be said that because some countries have retained their specifics, a unified system with the same rules has not been fully established. The paper presents and deals with the advantages and disadvantages of a single system (securing) of cross - border transport of cash under the said Regulation. The Republic of Serbia, as a country on the path to EU membership, has a special interest in getting to know and preparing in time for the harmonization of its legal solutions and practices which regulate the mentioned area (activity) of private security.
Keywords: private security, harmonization, cash-in-trasit, cross-border road transport of euro cash, European Union.